Implementing the Principles of Andragogy in ELT to Enhance the students’ English Competence - Syamsuddin Syamsuddin; Andi Asiz Jimi (EDUVELOP, 2018)
Various methods and activities have been undertaken by English teachers to improve the ability of students in English, but the reality shows that a monotonous and tedious method causes students to become passive. This study aims to determine the effect of using the principles of andragogy on the motivation and ability of English speaking students at the Faculty of Law, University of Sawerigading Makassar. The data in this study were obtained through oral tests given in the initial and final tests. The author also uses a questionnaire filled by 25 students from the experimental class. Data obtained from oral tests were then analyzed and interpreted using the SPSS 16 program, while questionnaires were analyzed and interpreted using a Likert scale. The results showed that the treatment given to the experimental class succeeded in improving students' English proficiency. The questionnaire results also show that the average value obtained is 90.16 and can be classified as "very interested". This indicates that the students in the experimental class responded positively to the method used. Keywords: principles of andragogy, student ability, motivation, English.